Polyphenylene sulfide composite material and preparation method thereof

By using polydopamine-grafted siloxane structure to encapsulate polyphenylene sulfide particles, the water dispersion and bonding properties are improved, and the problems of poor resin fluidity and uncontrolled slurry concentration in the preparation of PPS prepreg tape are solved. The stable preparation and continuous production of high fiber content prepreg tapes are achieved.

CN119463180APending Publication Date: 2025-02-18NANJING SPECIAL PLASTIC COMPOSITE MATERIALS CO LTD

Patent Information

Application Number
CN202411367173.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art has problems such as poor resin fluidity, difficult molding process and uncontrolled slurry concentration when preparing PPS prepreg tapes with high fiber content, which affects product quality and continuous production.

Method used

Polydopamine grafted with silicone network structure is used as a carrier to wrap polyphenylene sulfide particles to improve their water dispersion and bonding properties, thereby preparing high fiber content pre-impregnation through slurry suspension impregnation and heat treatment. With composite material.

Benefits of technology

The stability of the mud suspension is significantly improved, the resin heat-tight roller phenomenon is avoided, the stability of the fiber content of the prepreg belt is ensured, and continuous production is promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463180A_ABST
    Figure CN119463180A_ABST
Patent Text Reader

Abstract

The invention discloses a polyphenylene sulfide composite material and a preparation method thereof.The composite material is a continuous fiber reinforced thermoplastic resin prepreg tape and is prepared through a suspension impregnation method, and the preparation method comprises the steps that 1, thermoplastic resin suspension is prepared; (2) spreading and dipping fibers; and (3) a heat treatment process. The thermoplastic resin suspension is composed of thermoplastic resin powder, water and an additive. The thermoplastic resin powder is granular and has a'core-shell 'structure. The core is polyphenylene sulfide (PPS), and the particle size is 1-50 [mu] m; the shell comprises polydopamine and organic-inorganic composite lipid, and a polydopamine coating layer is rich in phenolic hydroxyl groups and nitrogen-containing functional groups, so that the originally inert PPS surface is activated, a foundation is laid for uniformly dispersing PPS powder in water, and the hydrophilicity of PPS is greatly improved; the polydopamine coating layer is further grafted with a siloxane structure, and the siloxane grid structure can improve the bonding strength of PPS, so that the bonding performance of the fiber and PPS resin is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a fiber-reinforced resin composite material, in particular to a polyphenylene sulfide composite material and a preparation method thereof. Background Art

[0002] Continuous fiber reinforced resin-based composite materials are composed of resin matrix and fiber reinforcement. The two parts interact and strengthen each other, so they have incomparable advantages over single-component resin or fiber. According to the different matrix resins, advanced resin-based composite materials can be divided into thermosetting composite materials and thermoplastic composite materials. Among them, thermoplastic composite materials with excellent mechanical properties and recyclable processing are becoming more and more the trend of the market.

[0003] However, the large-scale production of thermoplastic fiber prepregs in my country is currently in its infancy, and there is no large-scale thermoplastic fiber prepreg production line that can operate stably. The main processes for preparing thermoplastic prepregs include powder method, slurry method, film method, solution method, melt extrusion method, etc. Among them, when high melting point and high viscosity resins (such as PEEK, PPS, etc.) are used to prepare prepreg tapes by melt extrusion, there will be problems such as poor resin fluidity and difficult molding process, and this high viscosity resin cannot be used to prepare prepreg tapes with high fiber content. Moreover, polyphenylene sulfide (PPS) is a high-temperature resistant resin with excellent performance, and no solvent has been found to dissolve it at 200°C. Therefore, the solution method and powder impregnation process have high equipment prices and subsequent maintenance costs, which affect the popularity of PPS prepreg tapes.

[0004] At present, the main process for preparing PPS prepreg with high fiber content is the slurry suspension process, but the slurry concentration is not controlled during the production process, which directly affects the product quality and continuous production. Patent CN110641047A discloses a concentration adjustment system for preparing prepreg by slurry method. The system device includes a buffer tank, a slurry dispersion tank, a high-concentration slurry storage tank, etc. The system is complex and requires real-time concentration detection and liquid replenishment operations. Summary of the invention

[0005] In order to solve the deficiencies of the prior art, the present invention aims to provide a polyphenylene sulfide composite material and a preparation method thereof, using polydopamine grafted with a siloxane network structure as a carrier to encapsulate polyphenylene sulfide particles to improve the water dispersibility and bonding properties of polyphenylene sulfide resin powder and greatly improve the stability of the mud suspension. After the fiber is impregnated with the mud suspension and heat-treated, a prepreg tape composite material is prepared.

[0006] A polydopamine-siloxane composite modified polyphenylene sulfide resin, wherein the resin has a "core-shell" structure, wherein the core is polyphenylene sulfide (PPS) with a particle size of 1-50um; the shell comprises polydopamine and an organic-inorganic composite lipid, the polydopamine coating layer is rich in phenolic hydroxyl groups and nitrogen-containing functional groups, and the polydopamine coating layer is also grafted with a siloxane structure.

[0007] The preparation method of the polydopamine-siloxane composite modified polyphenylene sulfide resin comprises the following steps: S1. Add dopamine hydrochloride powder into deionized water and stir to dissolve, then add a certain amount of tris(hydroxymethyl)aminomethane to adjust the pH of the solution to 8-9, preferably to 8.5; S2, adding polyphenylene sulfide PPS material to the alkaline solution of dopamine hydrochloride, stirring the reaction until the solution completely turns black, washing with deionized water and ethanol until the solution becomes clear, and taking out the filter material; S3, dispersing the organic-inorganic composite lipid and the filter material obtained in S2 in ethanol, removing the solvent by rotary evaporation, and drying to obtain a polydopamine-siloxane composite modified polyphenylene sulfide resin.

[0008] The mass ratio of dopamine hydrochloride powder: polyphenylene sulfide PPS material: silicon-containing organic-inorganic composite lipid is 50-100:100:10-30.

[0009] The molecular formula of the organic-inorganic composite lipid is as follows: .

[0010] The preparation method of the organic-inorganic composite lipid is: S1: After dissolving hexadecylamine in anhydrous ethanol, add hexadecane bromide and potassium carbonate in sequence, heat under reflux and stir at 70-90°C for 100-150 h, then filter and wash twice, and recrystallize multiple times with a mixed solution of ethanol and n-hexane (1:3), and the obtained crystals are product A; S2: Add product A and itaconic anhydride to tetrahydrofuran solution, heat and dissolve completely, continue stirring and reacting for 12-36 hours, remove the solvent by rotary evaporation under vacuum conditions, and finally crystallize with acetonitrile to obtain a white solid, which is product B; S3: Dissolve product B in dichloromethane solution, add aminopropyltriethoxysilane and an appropriate amount of catalyst 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, stir and react at room temperature for 2-6 hours, remove the solvent by rotary evaporation, and purify by column chromatography to obtain an oily product which is a silicon-containing organic-inorganic composite lipid molecule.

[0011] The synthetic route of silicon-containing organic-inorganic composite lipid molecules is shown in the following formula:

[0012] The polydopamine-siloxane composite modified polyphenylene sulfide suspension is prepared by uniformly mixing the polydopamine-siloxane composite modified polyphenylene sulfide resin, emulsifier and water in a certain proportion and shearing and emulsifying to obtain an emulsion-like mud suspension; the suspension is an aqueous mud liquid, which is suitable for various continuous fibers and powdered resins of different particle sizes. The suspension can be stably placed for 48 hours without precipitation, and the fiber content of the prepreg tape can be kept stable without concentration adjustment during the production process.

[0013] The mass ratio of the polydopamine-siloxane composite modified polyphenylene sulfide resin to the emulsifier is 100:3-7.5; the mass ratio of the polydopamine-siloxane composite modified polyphenylene sulfide resin to water is 8-60:100; The emulsifier is a nonionic surfactant, including at least one of polyethylene glycol fatty acid esters, fatty alcohol polyoxyethylene ethers, and polyglycerol fatty acid esters.

[0014] A polyphenylene sulfide composite material, the composite material is a continuous fiber reinforced thermoplastic resin prepreg tape, prepared by a suspension impregnation method; specifically, polydopamine grafted with a siloxane network structure is used as a carrier to encapsulate polyphenylene sulfide particles, and the composite material is prepared by a suspension impregnation method; The main processes include: (1) preparation of thermoplastic resin suspension; (2) Spinning and impregnation of fibers; (3) Heat treatment process.

[0015] The thermoplastic resin suspension consists of thermoplastic resin powder, water and additives.

[0016] The thermoplastic resin powder is granular and has a "core-shell" structure. The core is polyphenylene sulfide (PPS) with a particle size of 1-50um; the shell includes polydopamine and organic-inorganic composite lipids. The polydopamine coating layer is rich in phenolic hydroxyl groups and nitrogen-containing functional groups, which activates the originally inert PPS surface and lays a foundation for the uniform dispersion of PPS powder in water, greatly improving the hydrophilicity of PPS; the polydopamine coating layer is also grafted with a siloxane structure. This siloxane grid structure can improve the bonding strength of PPS, thereby improving the bonding performance between the fiber and the PPS resin.

[0017] The preparation method of the polyphenylene sulfide composite material comprises the following specific steps: (1) Weigh the modified polyphenylene sulfide resin and emulsifier (mass ratio 100:3-7.5), mix them evenly with water in a certain proportion (mass ratio of modified polyphenylene sulfide powder to water = 8-60:100), and after shear emulsification for 10-20 minutes, obtain an emulsion-like mud suspension.

[0018] (2) The continuous fiber is pulled out from the yarn frame, passed through the yarn spreading device, and immersed in the mud suspension for sizing.

[0019] (3) The sizing fibers are directly shaped, pulled and rolled after heat treatment to prepare continuous fiber reinforced polyphenylene sulfide prepreg tapes with a width of 10-600 mm.

[0020] Preferably, in the aforementioned step (1), the emulsifier is a non-ionic surfactant, including at least one of polyethylene glycol fatty acid esters, fatty alcohol polyoxyethylene ethers, and polyglycerol fatty acid esters.

[0021] Preferably, in the aforementioned step (1), the modified polyphenylene sulfide material is a dopamine-modified PPS resin grafted with a siloxane structure (polydopamine-siloxane composite-modified polyphenylene sulfide resin), and the preparation method comprises the following steps: a. A certain mass of dopamine hydrochloride powder is added to deionized water and stirred to dissolve, and then a certain amount of tris (hydroxymethyl) aminomethane is added to adjust the pH of the solution to 8.5; b. Add PPS material to the prepared dopamine alkaline solution and continue to stir the reaction. It can be found that the color of the solution slowly changes from colorless to orange and finally completely turns black, indicating that the dopamine in the solution is gradually undergoing oxidative self-polymerization to form polydopamine. Wait for the reaction to occur at room temperature for 24 hours, rinse with deionized water and ethanol until the solution becomes clear, and remove the filter material; c. Weigh a certain amount of silicon-containing organic-inorganic composite lipid and the above filter material and disperse them in ethanol, remove the solvent by rotary evaporation, and finally dry them in a vacuum drying oven at 50°C to obtain dopamine-modified PPS resin grafted with a siloxane structure. The mass ratio is: dopamine hydrochloride powder: PPS: silicon-containing organic-inorganic composite lipid = 50-100: 100: 10-30.

[0022] Preferably, in the aforementioned step (1), the preparation steps of the silicon-containing organic-inorganic composite lipid are as follows: S1: Weigh 30.7 g of hexadecylamine and dissolve it in 100 mL of anhydrous ethanol, then add 19.8 g of hexadecane bromide and 27.3 g of potassium carbonate, heat under reflux and stir at 80°C for 120 h. Then filter and wash twice, and recrystallize several times with a mixed solution of ethanol and n-hexane (1:3), and the obtained crystals are product A.

[0023] S2: Weigh 3.0 g of product A and 1.29 g of itaconic anhydride and add them to 50 mL of tetrahydrofuran solution. Heat at 40°C until completely dissolved and continue stirring for 24 h. Remove the solvent by rotary evaporation under vacuum conditions, and finally crystallize with acetonitrile to obtain a white solid, which is product B.

[0024] S3: Weigh 2.0 g of product B and dissolve it in 50 mL of dichloromethane solution, then add 0.88 g of aminopropyltriethoxysilane and an appropriate amount of catalyst 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, stir the reaction at room temperature for 4 hours, remove the solvent by rotary evaporation, and purify by column chromatography to obtain an oily product which is a silicon-containing organic-inorganic composite lipid molecule.

[0025] Preferably, in the aforementioned step (2), the continuous fiber refers to one of carbon fiber, glass fiber, basalt fiber, etc.; Preferably, in the aforementioned step (2), the impregnation sizing is completed in an impregnation tank, in which three impregnation rods are provided. When the fiber is pulled, the impregnation rods alternately run up and down to perform sizing. The outlet of the impregnation tank is guided by a rotatable roller to avoid the backflow of the liquid and ensure the concentration stability of the suspension in the impregnation tank.

[0026] Preferably, the heat treatment conditions in the aforementioned step (3) are as follows: a 2m long 500°C heat radiation channel is used to dry the moisture, and then the resin is melted by a 1m long 700°C heat radiation channel, and then the resin is pressed by hot and cold rollers.

[0027] The beneficial effects of the present invention are: (1) The suspension prepared by the present invention is an aqueous slurry without any organic solvent added, can be operated at room temperature, and is suitable for various continuous fibers as well as powdered resins of different particle sizes.

[0028] (2) The main technical bottleneck of the slurry process is that the concentration of resin slurry is not controlled: when the fiber passes through the dipping tank, a large amount of resin powder is taken away, resulting in the slurry concentration in the dipping tank gradually becoming thinner as the production time increases. The prepreg resin content cannot be kept constant, which directly affects the product quality and continuous industrial production. The suspension prepared by the present invention can be placed stably for 48 hours without precipitation. The fiber content of the prepreg tape can be kept stable without concentration adjustment during the production process, breaking through the technical bottleneck of uncontrolled slurry concentration during the production process.

[0029] (3) The resin of the PPS prepreg tape is prone to sticking to the hot roller during the shaping and preparation process. The silicone grid structure of the PPS shell of the present invention improves its bonding performance, improves the bonding effect between the fiber and PPS, avoids the bonding phenomenon with the hot roller, and promotes its continuous production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Example 1 Preparation of PPS suspension; Figure 2 Comparative Example 1 Preparation of PPS suspension; Figure 3 Microscope images of the suspensions of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. Example 1

[0032] (1) Add a certain amount of dopamine hydrochloride powder to deionized water and stir to dissolve, then add a certain amount of tris(hydroxymethyl)aminomethane to adjust the pH of the solution to 8.5, add PPS material to the prepared dopamine alkaline solution, continue stirring to react, and it can be found that the color of the solution slowly changes from colorless to orange, and finally completely turns black, indicating that the dopamine in the solution is gradually undergoing oxidative self-polymerization to form polydopamine. After the reaction is at room temperature for 24 hours, rinse with deionized water and ethanol until the solution becomes clear, and remove the filter material; Weigh a certain amount of silicon-containing organic-inorganic composite lipid and the above-mentioned filter material, disperse them in ethanol, remove the solvent by rotary evaporation, and finally dry them in a vacuum drying oven at 50°C to obtain dopamine-modified PPS resin grafted with a siloxane structure, with a mass ratio of dopamine hydrochloride powder: PPS: silicon-containing organic-inorganic composite lipid = 50:100:10.

[0033] Weigh the modified polyphenylene sulfide resin and polyethylene glycol-400, mix them evenly with water, the mass ratio of modified polyphenylene sulfide resin: polyethylene glycol-400: water = 15:0.91:100, and after shear emulsification for 20 minutes, an emulsion mud suspension with a resin concentration of 15% is obtained.

[0034] (2) 56 12K T300 carbon fibers were pulled out from the creel, stretched to a width of 310 mm by a yarn spreading device, and immersed in a slurry suspension with a PPS resin concentration of 15% for sizing.

[0035] (3) The sizing fibers pass through a 2-m-long 500°C heat radiation channel to dry out moisture, and then enter a 1-m-long 700°C heat radiation channel to melt the resin. After that, they are pressed by hot and cold rollers and pulled and rolled to produce a 300-mm-wide continuous carbon fiber reinforced polyphenylene sulfide prepreg tape.

[0036] The steps for preparing the silicon-containing organic-inorganic composite lipid molecule are as follows: S1: Weigh 30.7 g of hexadecylamine and dissolve it in 100 mL of anhydrous ethanol, then add 19.8 g of hexadecane bromide and 27.3 g of potassium carbonate, heat under reflux and stir at 80°C for 120 h. Then filter and wash twice, and recrystallize several times with a mixed solution of ethanol and n-hexane (1:3), and the obtained crystals are product A.

[0037] S2: Weigh 3.0 g of product A and 1.29 g of itaconic anhydride and add them to 50 mL of tetrahydrofuran solution. Heat at 40°C until completely dissolved and continue stirring for 24 h. Remove the solvent by rotary evaporation under vacuum conditions, and finally crystallize with acetonitrile to obtain a white solid, which is product B.

[0038] S3: Weigh 2.0 g of product B and dissolve it in 50 mL of dichloromethane solution, then add 0.88 g of aminopropyltriethoxysilane and an appropriate amount of catalyst 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, stir the reaction at room temperature for 4 hours, remove the solvent by rotary evaporation, and purify by column chromatography to obtain an oily product which is a silicon-containing organic-inorganic composite lipid molecule.

[0039] Comparative Example 1 The difference from Example 1 is that the polyphenylene sulfide powder particles do not have a polydopamine coating layer.

[0040] (1) Weigh a certain amount of silicon-containing organic-inorganic composite lipid and PPS powder and disperse them in ethanol, remove the solvent by rotary evaporation, and finally dry them in a vacuum drying oven at 50°C to obtain siloxane-modified PPS resin, with a mass ratio of PPS:silicon-containing organic-inorganic composite lipid = 100:10.

[0041] Weigh the modified polyphenylene sulfide resin and polyethylene glycol-400, mix them evenly with water, the mass ratio of modified polyphenylene sulfide resin: polyethylene glycol-400: water = 15:0.91:100, and after shear emulsification for 20 minutes, an emulsion mud suspension with a resin concentration of 15% is obtained.

[0042] (2) 56 12K T300 carbon fibers were pulled out from the creel, stretched to a width of 310 mm by a yarn spreading device, and immersed in a slurry suspension with a PPS resin concentration of 15% for sizing.

[0043] (3) The sizing fibers pass through a 2-m-long 500°C heat radiation channel to dry out moisture, and then enter a 1-m-long 700°C heat radiation channel to melt the resin. After that, they are pressed by hot and cold rollers and pulled and rolled to produce a 300-mm-wide continuous carbon fiber reinforced polyphenylene sulfide prepreg tape.

[0044] The preparation steps of the silicon-containing organic-inorganic composite lipid molecule are the same as those in Example 1.

[0045] Comparative Example 2 The difference from Example 1 is that the polydopamine coating layer outside the polyphenylene sulfide powder particles has no siloxane structure.

[0046] (1) Add a certain amount of dopamine hydrochloride powder to deionized water and stir to dissolve, then add a certain amount of tris(hydroxymethyl)aminomethane to adjust the pH of the solution to 8.5, add PPS material to the prepared dopamine alkaline solution, continue stirring to react, and it can be found that the color of the solution slowly changes from colorless to orange, and finally completely turns black, indicating that the dopamine in the solution is gradually undergoing oxidative self-polymerization to form polydopamine. After the reaction is at room temperature for 24 hours, rinse with deionized water and ethanol until the solution becomes clear, take out the filter material, and dry it in a vacuum drying oven at 50°C to obtain polydopamine-modified PPS resin, with a mass ratio of dopamine hydrochloride powder: PPS = 50:100.

[0047] Weigh the modified polyphenylene sulfide resin and polyethylene glycol-400, mix them evenly with water, the mass ratio of modified polyphenylene sulfide resin: polyethylene glycol-400: water = 15:0.91:100, and after shear emulsification for 20 minutes, an emulsion mud suspension with a resin concentration of 15% is obtained.

[0048] (2) 56 12K T300 carbon fibers were pulled out from the creel, stretched to a width of 310 mm by a yarn spreading device, and immersed in a slurry suspension with a PPS resin concentration of 15% for sizing.

[0049] (3) The sizing fibers pass through a 2-m-long 500°C heat radiation channel to dry out moisture, and then enter a 1-m-long 700°C heat radiation channel to melt the resin. After that, they are pressed by hot and cold rollers and pulled and rolled to produce a 300-mm-wide continuous carbon fiber reinforced polyphenylene sulfide prepreg tape.

[0050] The preparation steps of the silicon-containing organic-inorganic composite lipid molecule are the same as those in Example 1.

[0051] Test analysis 1. Stability analysis In order to prove the stability of the polyphenylene sulfide suspension modified by polydopamine-siloxane composite, the suspension samples prepared in Example 1 and Control Example 1 were used as controls to observe the state of the suspension after different standing times to study the effect of modification on the stability of the suspension. Figure 1 The following are the PPS suspension (a) prepared in Example 1, and the dispersion after standing for (b) 1 h, (c) 3 h, (d) 12 h, (e) 24 h, and (f) 48 h. No stratification or agglomeration was observed in the suspension even after standing for 48 h. Figure 2 As shown, after 30 minutes of standing, the solid powder in the suspension was almost completely precipitated at the bottom of the bottle, indicating that the PPS suspension system prepared in Example 1 of the present invention is relatively stable.

[0052] 2. Fiber content stability In order to further prove the stability of the suspension, the fiber content of the prepreg tape in continuous production is tested to evaluate the concentration stability of the suspension during production. In continuous production, if the fiber content of the prepreg tape gradually increases, it means that the resin attached to the fiber is decreasing, the concentration of the suspension it is impregnated with is slowly decreasing, or the concentration of the upper layer of the suspension is low due to precipitation. The fiber content is calculated as follows: Fiber mass content = (number of fibers × fiber weight) / weight of prepreg tape per meter × 100% As can be seen from Table 1, when Example 1 was continuously produced on the production line, the effect of the suspension on the fiber content was within the normal fluctuation range, and the fiber content was 67%±3. When the control example 1 was continuously produced on the production line, as time went by, the fiber mass content continued to increase, and the resin attached to the fiber slowly decreased. After 30 minutes of production, the fiber content rose to 80.1%. After that, due to the lack of resin and severe bifurcation of the prepreg, production could no longer be carried out.

[0053] Table 1 Statistical table of fiber mass content

[0054] 3. Suspension dispersion analysis Figure 3 In the suspension prepared in Example 1, PPS dispersion was relatively uniform under microscope observation, with basically no agglomeration phenomenon; in the suspension prepared in Control Example 1 in which PPS powder particles were not coated with a polydopamine layer, it was observed that the particles agglomerated more seriously, indicating that the polydopamine coating layer was rich in phenolic hydroxyl groups and nitrogen-containing functional groups, which activated the originally inert PPS surface, increased the hydrophilicity of PPS to a certain extent, and improved its water dispersion effect.

[0055] 4. Shear performance analysis The prepreg tape 0° / 90° laminate was molded into a 2mm thick plate, and water-cut into 25mm×250mm specimens. The shear strength and modulus of the specimens were tested at a rate of 2mm / min using an MTS10T universal testing machine.

[0056] The shear strength of the continuous carbon fiber reinforced polyphenylene sulfide prepreg prepared in Control Example 2 is relatively low, indicating that the bonding strength between the carbon fiber and the PPS resin in the prepreg prepared in Example 1 is relatively high, and interlayer peeling is relatively difficult, so the shear strength is relatively high. The possible reason is that the polydopamine coating layer of PPS has a siloxane structure, and this siloxane grid structure can improve the bonding performance of PPS, thereby improving the bonding strength between the fiber and the resin.

[0057] Table 2 Shear test data statistics

[0058] The above embodiments do not limit the protection scope of the present invention.

Claims

1. A polyphenylene sulfide resin compositely modified with polydopamine and siloxane, characterized in that: The resin has a "core-shell" structure, wherein the core is polyphenylene sulfide, the shell comprises polydopamine and organic-inorganic composite lipids, and the polydopamine coating layer is grafted with a siloxane structure.

2. The method for preparing the polydopamine-siloxane composite modified polyphenylene sulfide resin according to claim 1, characterized in that: The steps include: S1, the dopamine hydrochloride powder was added to deionized water and stirred to dissolve, and then a certain amount of tris (hydroxymethyl) aminomethane was added to adjust the pH of the solution to 8 ~ 9; S2, adding polyphenylene sulfide PPS material to the alkaline solution of dopamine hydrochloride, stirring the reaction until the solution completely turns black, washing with deionized water and ethanol until the solution becomes clear, and taking out the filter material; S3, dispersing the organic-inorganic composite lipid and the filter material obtained in S2 in ethanol, removing the solvent by rotary evaporation, and drying to obtain a polydopamine-siloxane composite modified polyphenylene sulfide resin.

3. The method for preparing the polydopamine-siloxane composite modified polyphenylene sulfide resin according to claim 2, characterized in that: The mass ratio of dopamine hydrochloride powder: polyphenylene sulfide PPS material: silicon-containing organic-inorganic composite lipid is 50-100:100:10-30.

4. The method for preparing the polydopamine-siloxane composite modified polyphenylene sulfide resin according to claim 2, characterized in that: The molecular formula of the organic-inorganic composite lipid is as follows: 。 5. A polyphenylene sulfide composite material comprising the polyphenylene sulfide resin modified by the polydopamine-siloxane composite according to claim 1.

6. The method for preparing the polyphenylene sulfide composite material according to claim 5, characterized in that: The steps include: (1) Weigh the polydopamine-siloxane composite modified polyphenylene sulfide resin, emulsifier and water, mix them evenly, and shear emulsify for 10-20 minutes to obtain an emulsion mud suspension; (2) dipping the continuous fibers into the slurry suspension prepared in step (1) for sizing; (3) The sizing fibers are directly shaped, pulled and rolled after heat treatment to prepare a continuous fiber reinforced polyphenylene sulfide prepreg tape of a certain width.

7. The method for preparing a polyphenylene sulfide composite material according to claim 6, characterized in that: In step (1), the mass ratio of the polydopamine-siloxane composite modified polyphenylene sulfide resin to the emulsifier is 100:3-7.5; the mass ratio of the polydopamine-siloxane composite modified polyphenylene sulfide resin to water is 8-60:

100.

8. The method for preparing a polyphenylene sulfide composite material according to claim 6, characterized in that: In step (1), the emulsifier is at least one of polyethylene glycol fatty acid esters, fatty alcohol polyoxyethylene ethers, and polyglycerol fatty acid esters.

9. The method for preparing a polyphenylene sulfide composite material according to claim 6, characterized in that: In step (2), the continuous fiber refers to one of carbon fiber, glass fiber and basalt fiber.

10. The method for preparing a polyphenylene sulfide composite material according to claim 6, characterized in that: In step (3), the heat treatment conditions are: first entering a 2m long 500°C heat radiation channel to dry the moisture, then entering a 1m long 700°C heat radiation channel to melt the resin, and then passing through a hot and cold roller press molding.

Citation Information

Patent Citations

  • Production system for preparing thermoplastic prepreg through mud method

    CN110641047A

Cited By

  • Bionic graft polymer as well as preparation method and application thereof

    CN121718029A